Mindfulness and Coping Skills as Predictors of Competitive Anxiety amongst Athletes in Indonesia - Didon Permadi; Fivi Nurwianti (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
Competitive anxiety is one of the psychological factors which greatly affect athletes' performances. Competitive anxiety is divided into somatic anxiety and cognitive anxiety. This study was conducted to look at mindfulness and coping skills as predictors of competitive anxiety. Through purposive sampling techniques, some (N = 159) senior athletes, representatives of various sports from various provinces in Indonesia, with an age range of 18-40 years were included in this study. This non-experimental research method design used three questionnaires, consisting of AAQ-II (mindfulness), ACSI (coping skills), and CSAI-2R (competitive anxiety) as measurement tools. Statistical analysis, using multiple regression, showed that mindfulness and coping skills simultaneously have a linear relationship to competitive anxiety, and significantly predict a competitive anxiety level of 29%. This means that mindfulness and coping skills can decrease competitive anxiety in athletes. Further analysis found that mindfulness plays a greater role in reducing competitive anxiety than coping skills.